2019
DOI: 10.3390/rs11080923
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Changes of Forest Structural Attributes at Three Different Spatial Aggregation Levels in Northern California using Multitemporal LiDAR

Abstract: Accurate estimates of growth and structural changes are key for forest management tasks such as determination of optimal rotation times, optimal rotation times, site indices and for identifying areas experiencing difficulties to regenerate. Estimation of structural changes, especially for biomass, is also key to quantify greenhouse gas (GHG) emissions/sequestration. We compared two different modeling strategies to estimate changes in V, BA and B, at three different spatial aggregation levels using auxiliary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…A large number of studies have demonstrated the value of multi-temporal ALS data for estimating changes in forest attributes [12,16,73]. Change maps are important for understanding the state and dynamics of forests, and they can be used as an initial information source for reporting carbon emissions.…”
Section: Population Changementioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have demonstrated the value of multi-temporal ALS data for estimating changes in forest attributes [12,16,73]. Change maps are important for understanding the state and dynamics of forests, and they can be used as an initial information source for reporting carbon emissions.…”
Section: Population Changementioning
confidence: 99%
“…Zhao et al [14] estimated ∆AGB in a forested landscape in Scotland with the indirect approaches showing slightly more precise performances. In addition, the indirect modeling has been claimed to be less sensitive to extrapolating and it has been found to be a better alternative to estimate changes more accurately at stand-level [73]. In light of the diversity of results, the most accurate and/or precise approach may have to be determined by the data available for each study.…”
Section: Population Changementioning
confidence: 99%
“…Models that predict change directly tend to be more accurate than those that predict change indirectly [18,53,54], but the flexibility of applying a single model to multiple image dates with the indirect method is often thought to outweigh the problems (e.g., Powell et al [55]). In many cases, ground measurements of change are not available, and indirect estimation of change is the only option (e.g., Andersen et al [56]).…”
Section: Modeling C Stocks and Stock Change With Only Spatial Predictorsmentioning
confidence: 99%
“…Regardless of the source of RS data and the type of extracted features from this data, an area-based approach (ABA) is the most appropriate method for AGB estimation over large areas [32,33]. This is because ABA makes it possible to obtain model-unbiased estimates of AGB [34], and the requirements for RS data (e.g., point cloud density) or hardware are relatively low [32]. On the other hand, up-to-date ground data are still needed for preparing a model, and when tree-level information, such as stem number or species, is desired, ABA is less suitable [35].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have used different RS data and modelling methods to predict AGB in forest, shrub, or grassland ecosystems (e.g., [10,[32][33][34][35][38][39][40][41][42]). However, as far as we know, relatively few studies (e.g., [22,23,26]) have dealt with the spatial identification of AAL and prediction of AGB on AAL using ALS data.…”
Section: Introductionmentioning
confidence: 99%